Enhancing Compatibility and Mechanical Properties of Natural Rubber Composites - Sianturi, Krisma Yessi; Nugraha, Adam Febriyanto; kristaura, Belle; Chalid, Mochamad (UI Scholars Hub, 2023)
Pure natural rubber (NR) exhibits low mechanical properties, necessitating the incorporation of additives like vulcanizing agents and fillers. Carbon black and silica, conventional fillers, are relatively expensive and not environmentally friendly. This study explores using Oil Palm Empty Fruit Bunch (OPEFB) fiber as an affordable, abundant, and biodegradable alternative filler for NR. However, compatibility issues arise between the nonpolar NR and the polar OPEFB fiber. A latex-starch hybrid coupling agent (CA (NR-St)) was added to the composite formulation to address this. NR, OPEFB fiber, and the coupling agent were mixed using an open roll mill with a 10 phr OPEFB filler loading and coupling agent concentrations of 0, 1, 2, and 3 phr. Fourier-transform infrared spectroscopy (FTIR), rheology, and mechanical property tests revealed that the coupling agent improved the compatibility between NR and OPEFB fibers, as evidenced by increased tensile strength and stiffness. The composite with 3-phr coupling agent exhibited the best performance with tensile strength and stiffness values of 25.6 MPa and 3.7 MPa, respectively. This increase in mechanical properties has the potential to act as a catalyst for increasing the use of renewable materials in the rubber industrial sector, especially the automotive industry.